Comparison of ventilatory modes to facilitate liberation from mechanical ventilation: protocol for a systematic review and network meta-analysis. Issue 9 (5th September 2019) - Lewis, Kimberley A; Chaudhuri, Dipayan; Guyatt, Gordon; Burns, Karen E A; Bosma, Karen; Ge, Long; Karachi, Tim; Piraino, Thomas; Fernando, Shannon M; Ranganath, Nischal; Brochard, Laurent; Rochwerg, Bram
Abstract : Introduction: Timely liberation from invasive mechanical ventilation is important to reduce the risk of ventilator-associated complications. Once a patient is deemed ready to tolerate a mode of partial ventilator assist, clinicians can use one of multiple ventilatory modes. Despite multiple trials, controversy regarding the optimal ventilator mode to facilitate liberation remains. Herein, we report the protocol for a systematic review and network meta-analysis comparing modes of ventilation to facilitate the liberation of a patient from invasive mechanical ventilation. Methods and analysis: We will search MEDLINE, EMBASE, PubMed, the Cochrane Library from inception to April 2019 for randomised trials that report on critically ill adults who have undergone invasive mechanical ventilation for at least 24 hours and have received any mode of assisted invasive mechanical ventilation compared with an alternative mode of assisted ventilation. Outcomes of interest will include: mortality, weaning success, weaning duration, duration of mechanical ventilation, duration of stay in the acute care setting and adverse events. Two reviewers will independently screen in two stages, first titles and abstracts, and then full texts, to identify eligible studies. Independently and in duplicate, two investigators will extract all data, and assess risk of bias in all eligible studies using the Modified Cochrane Risk of Bias tool. Reviewers will resolve disagreement by discussion and consultation with a third reviewer as necessary. Using a frequentist framework, we will perform random-effect network meta-analysis, including all ventilator modes in the same model. We will calculate direct and indirect estimates of treatment effect using a node-splitting procedure and report effect estimates using OR and 95% CI. We will assess certainty in effect estimates using Grading of Recommendations Assessment, Development and Evaluation methodology. Ethics and dissemination: Research ethics board approval is not necessary. The results will be disseminated through publication in a peer-reviewed journals. PROSPERO registration number: CRD42019137786